Corticoamigdalohipocampectomia para o tratamento da epilepsia refratária associada à esclerose mesial temporal - Meguins, Lucas Crociati (2014)
INTRODUCTION: Mesial temporal sclerosis (MTS) is the commonest surgical pathology associated with refractory temporal lobe epilepsy (TLE) with a percentage in series of temporal lobe resection ranging from 28% to 62%. OBJECTIVE: The aim of the present study is to describe the clinical and sociodemographic characteristics of patients with TLE-MTS submitted to cortico-amygdalohippocampectomy (CAH) and to investigate the influence of patient’s age at surgery and seizure onset on surgical outcome of TLE in a Brazilian tertiary epilepsy center. METHODS: A retrospective observational investigation was performed with data collection from a cohort of consecutive patients surgically treated in the epilepsy clinic of Faculdade de Medicina de Sao Jose do Rio Preto (FAMERP), a Brazilian tertiary referral epilepsy center, from January 2000 to March 2012. Patients were divided accordingly to their age at surgery (< or ≥50 years) and to epilepsy duration at surgery (< or > 10 years). RESULTS: Two hundred and twenty-nine patients were included. The mean age at surgery was of 39.9±11.57 years, with 105 (45.8%) male and 124 (54.2%) female. Two hundred and twenty-one (96.5%) patients were right-handed and eight (3.5%) left-handed. Thirty (13.1%) patients presented a previous history of febrile seizure during infancy and 27 (11.7%) reported head trauma before the beginning of refractory seizures. Thirty-six (16%) were taking a single anti-epileptic drug (AED) and 193 (84%) were taking two or more AEDs. Patients’ follow-up observed that 144 (62.8%) were classified as Engel I and 200 (87.5%) were classified as Engel I or II. Eleven patients (4.7%) were Engel III and 18 (7.8%) were Engel IV. At six, twelve and twenty-four months of followup, 144, 137 and 132 patients, respectively, were classified as Engel I. One-hundred and eleven of 179 patients (62%) were classified as Engel I in the group with <50 years old, whereas 33 of 50 (66%) as Engel I in the group with ≥50 years old group (p=0.82). From the total of patients seizure free (Engel I), 88 (61%) reported epilepsy duration inferior to 10 years and 56 (39%) superior to 10 years (p<0.01). From the total of patients not seizure free (Engel II, III and IV), 36 (42%) reported epilepsy duration inferior to 10 years and 49 (58%) superior to 10 years (p<0.01). There were no surgery-related significant neurological deficits or deaths. CONCLUSION: In the present study, we demonstrated that CAH is a safe and feasible surgical modality to effectively treat patients with refractory TLE-MTS. Additionally, it was observed that a shorter epilepsy duration at surgery is an important risk factor that must be considered before surgical management of MTS. Early recognition and surgical treatment of patients with refractory TLE-MTS may improve seizure outcome.